2011
DOI: 10.1007/s11126-011-9191-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Bipolar Depression: Qualitative Systematic Review of Double-Blind Randomized Clinical Trials

Abstract: Randomized clinical trial (RCT) is the best study design for treatment-related issues, yet these studies may present a number of biases and limitations. The objective of this study is to carry out a qualitative analysis of RCT methodology in the treatment of bipolar depression (BD). A systematic review covering the last 20 years was performed on PubMed selecting double-blind RCTs for BD. The identification items of the articles, their design, methodology, outcome and grant-related issues were all analyzed. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Some of the observed discrepancies between expert recommendations and real-life pharmacotherapy may also be due to the limitations of current randomized clinical trials as suggested by a recent systematic review (Spanemberg et al, 2011). The authors concluded that several articles on the pharmacological treatment of bipolar depression have methodological errors, biases and statistical simplifications, which complicate the extrapolation of the data to real-life settings.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the observed discrepancies between expert recommendations and real-life pharmacotherapy may also be due to the limitations of current randomized clinical trials as suggested by a recent systematic review (Spanemberg et al, 2011). The authors concluded that several articles on the pharmacological treatment of bipolar depression have methodological errors, biases and statistical simplifications, which complicate the extrapolation of the data to real-life settings.…”
Section: Discussionmentioning
confidence: 99%
“…Given limited data on the efficacy of primary or adjunctive treatments (ie, there are no gold standard effective treatments), direct comparisons without placebo were not included, and there are only a handful of such studies in any case. 14,15 The discussion that follows organizes treatments by medication class. The evidence for the efficacy of each medication is then discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[0-1]*, 296. [4][5][6][7][8]*, F30* and F31*) or SCAD (295.7* and F25*) during the observation period 2003-2015, and were newly given one of 29 drugs of interest, including lithium, mood-stabilizing anticonvulsants (MSAs), first-generation antipsychotics (FGAs), secondgeneration antipsychotics (SGAs), and antidepressants (ADs) (Supporting Information Table S1). Each drug of interest had at least 250 observations that met study design criteria.…”
Section: Patients and Me Thodsmentioning
confidence: 99%
“…The evidence on drug‐dependent risk of hospitalization in BD is incomplete and contradictory. The majority of published comparative effectiveness studies of BD drugs have focused on symptom reduction and rates of remission achievement, relapses and recurrences, rather than on psychiatric hospitalization . Comparison is usually made for just a few agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation